CREATIVE IMPLEMENTATION MODEL OF INCLUSIVE EDUCATION (Proceedings of International Conference on Special Education, 2017)
Inclusive Education, an ideology based on the new education philosophy which is humane, democratic, and non-discriminatory and for all. All the government systems in Gresik regency are very care to the Inclusive Education. Because of that, this great practical education should be socialized in order to motivate other country in implementation of Inclusive education. By using the creative model in the implementation of Inclusive Education, it can be proven by the Increasing of the pure participation number of children with special need about 131,6 percents and leading Gresik Regency awarded an inclusive Education award from National Education Ministry.